Pemilihan Supplier Industri Manufaktur Dengan Pendekatan AHP dan TOPSIS - Lukmandono Lukmandono; Minto Basuki; M Junaidi Hidayat; Viky Setyawan (OPSI, 2019)
The problem in this research is to determine the criteria and criteria weights from the suppliers. PT. KBP is a manufacturing company engaged in the manufacture of export shoes with the main raw material for leather and supporting raw material for heels. The products produced are various kinds of fashion model shoes for adult women, including boots, mid boots, sneakers, and sandals. During this time, the company set suppliers based on the price offered and the number of goods. This study aims to establish the criteria and sub-criteria used as aspects of consideration for selecting suppliers based on company conditions to produce the best supplier decisions. The method used in this study is AHP and TOPSIS. AHP is used as a weighting of criteria and sub-criteria, while TOPSIS is used to determine alternative priorities that are close to positive ideal solutions. This study uses seven criteria and 17 sub-criteria. The results with the AHP method obtained weighted price criteria 18.2%, quality 28.7%, delivery 11.1%, flexibility 9.9%, responsive 9.0%, performance history 10.9%, and warranty and claim policy 12.2% whereas the TOPSIS method was obtained for PT. B is 0.710, and for supplier, G heels are 0.537. Thus PT. KBP can prioritize PT. B, as the main supplier.